Plantas medicinais utilizadas em comunidades do município de Igarapé-Miri, Pará: etnofarmácia do município de Igarapé-Miri-Pará - PINTO, Lucianna do Nascimento (2008)
In IgarapéMiri, as well throughout the state of Pará, the use of medicinal plants to treat many illnesses is very usual. In the same way, in some states in Brazil official programs of medicinal plants have been registered and to follow the plant species used in the folk phytotherapy ethnoguided methodologies are applied mainly ethnobotany and ethnopharmacology. From the Pharmaceutical Sciences Ethopharmacy was elaborated, which has been worldwide used to approach medicinal plants and to evaluate the remedies prepared from them. The general aim of this work is to contribute for the consolidation of Ethnopharmacy and the implementation of the PNPMF in the state of Pará, bringing information collected about indication of medicinal plants, preparation and administration of vegetal remedies and problems related to the use of them. More specifically, it aims to determine the regional nosogeography, to identify and to select the used phytotherapeutical resources for the treatment of the prevalent illnesses, to know and to characterise from the pharmaceutical point of view the remedies made with vegetable base, as well as elaborating cards with information about selected vegetables, these are other objectives considered here. The tool to reach these objectives is the ethnopharmaceutical survey which associates elements of other ethnoguided methods with the content of the Pharmaceutical Care. Applied in eighty six communities of the city, at two moments, first in the year 2000 and in March/April 2008, the method supplied data which were tabulated using Excel to make tables and graphs. Thus, 91 illnesses, 236 plants species, distributed through 72 botanical families, and in 7 different forms of administration. Thirty eight adverse events could also be identified. Cards with botanical, chemical and ethnopharmaceutical information were elaborated for the four plants species with highest relative citation frequencies.